2022
DOI: 10.1002/ece3.9410
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the distributions of Scleroderma guani (Hymenoptera: Bethylidae) under climate change in China

Abstract: The wasp Scleroderma guani is an important parasitic natural enemy of a variety of stem borers such as longicorn beetles. Studying and clarifying the suitable area of this wasp plays an important role in controlling stem borers. Based on information about the actual distribution of S. guani and on a set of environmental variables, MaxEnt niche model and ArcGIS were exploited to predict the potential distribution of this insect in China. This work simulated the geographical distribution of potential climatic su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…In agreement with earlier studies on two species of hares ( Lepus capensis , Slimen et al., 2017 ; Lepus europaeus , Stefanovic et al., 2019 ), we found that the precipitation factors were the drivers of positive selection of mitochondrial genes in lacertid lizards. Bio3, Bio4, and Bio13 are the common bioclimatic variables affecting the distribution of animals and ecologically suitable niches (Deng et al., 2022 ; Gao et al., 2021 ; Moradi‐Asl et al., 2020 ; Ye et al., 2022 ). According to our research, these bioclimatic variables were mostly important for gene selection, and increased the adaptability to different environment of lizards.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with earlier studies on two species of hares ( Lepus capensis , Slimen et al., 2017 ; Lepus europaeus , Stefanovic et al., 2019 ), we found that the precipitation factors were the drivers of positive selection of mitochondrial genes in lacertid lizards. Bio3, Bio4, and Bio13 are the common bioclimatic variables affecting the distribution of animals and ecologically suitable niches (Deng et al., 2022 ; Gao et al., 2021 ; Moradi‐Asl et al., 2020 ; Ye et al., 2022 ). According to our research, these bioclimatic variables were mostly important for gene selection, and increased the adaptability to different environment of lizards.…”
Section: Discussionmentioning
confidence: 99%
“…One of the key contributions of our study is the use of the MaxEnt model to determine the distribution probability of G. sarpedon in China, which will effectively guide future field investigations, monitoring, and control efforts. While the MaxEnt model has the advantages of being easy to use, requiring small sample sizes, and providing high prediction accuracy, it also has some limitations; for example, response curves show only the effect of a single environmental factor, ignoring interactions between variables (Deng et al., 2022 ). In this study, we focused on the impact of climate on the distribution of G. sarpedon , and the environmental variables used in the MaxEnt model prediction, with the exception of altitude, were all climate variables.…”
Section: Discussionmentioning
confidence: 99%
“…The Maxent model used in this study has good performance among many prediction models [ 36 ], accurate prediction, simple operation, robust performance, and other advantages, but the use of the model is still not perfect [ 37 ]. The variables used in this study only involve temperature, rainfall and altitude, and other environmental impacts factors such as wind speed, airflow, air, and landform are not fully included in the model.…”
Section: Discussionmentioning
confidence: 99%